An Upper‐Bound Assessment of the Benefits of Reducing Perchlorate in Drinking Water. Issue 10 (5th September 2014) - Lutter, Randall
<x xml:space="preserve">Abstract</x> The Environmental Protection Agency plans to issue new federal regulations to limit drinking water concentrations of perchlorate, which occurs naturally and results from the combustion of rocket fuel. This article presents an upper‐bound estimate of the potential benefits of alternative maximum contaminant levels for perchlorate in drinking water. The results suggest that the economic benefits of reducing perchlorate concentrations in drinking water are likely to be low, i.e., under $2.9 million per year nationally, for several reasons. First, the prevalence of detectable perchlorate in public drinking water systems is low. Second, the population especially sensitive to effects of perchlorate, pregnant women who are moderately iodide deficient, represents a minority of all pregnant women. Third, and perhaps most importantly, reducing exposure to perchlorate in drinking water is a relatively ineffective way of increasing iodide uptake, a crucial step linking perchlorate to health effects of concern.